Synthesis and structure of an anionic Ga26R8 cluster with a metalloid core - Rodig, Alexander; Linti, Gerald W. (Angewandte Chemie. International edition, 2000)
A section of the gallium high‐pressure modification GaIII is represented by the metalloid cluster core (see picture) of the Ga26 cluster anion, which forms along with further gallium cluster compounds,...